Helminths From an Introduced Species (Tupinambis merianae), and Two Endemic Species (Trachylepis atlantica and Amphisbaena ridleyi) From Fernando de Noronha Archipelago, Brazil - Ramalho, A. C. O. [UNESP]; da Silva, R. J. [UNESP]; Schwartz, H. O. [UNESP]; Peres, A. K. [UNESP] (Amer Soc Parasitologists, 2009)
The present study reports the occurrence of helminths in the introduced species Tupinambis merianae (tegu lizard), and in two endemic species Trachylepis atlantica (small lizard) and Amphisbaena ridleyi (two-head-snake lizard), from Fernando de Noronha Archipelago, State of Pernambuco, Brazil. Nine species of helminths were found, mainly in the digestive tract and accessory organs, with the following prevalence (P) and mean infection intensity (MII). Tupinambis merianae: Diaphanocephalus galeatus (P = 96%, MII = 20.5), Spinicauda spinicauda (P = 100%, MII = 197.8), and Oochoristica sp. 1 (P = 20%, MII = 4.4). Trachylepis atlantica: Moaciria alvarengai (P = 20%, MII = 1.4), S. spinicauda (P = 92%, MII = 22.1), Mesocoelium monas (P = 4%, MII = 3.0), Platynosomum sp. (P = 8%, MII = 7.0), and Oochoristica sp.2 (P = 16%, MII = 1.25). Amphisbaena ridleyi: Aplectana albae (P = 96%, MII = 143.4), Thelandros alvarengai (P = 4%, MII = 1.0), Me. monas (P 44%, MII = 2.8), Platynosomum sp. (P = 36%; MII = 13.8), and Oochoristica sp.2 (P = 48%; MII = 2.17). More than 80% of T. merianae were infected with 2, or more, helminth species. In Tr. atlantica, single-species infections were present in 50% of the specimens, but co-occurrence of 2 parasites was also high (41.7%). In A. ridleyi, multiple infections were more common, with up to 5 parasite species present. The helminth fauna observed allowed us to conclude that helminths can be carried together with their host when they colonize new geographic localities and that these introduced helminths can, in turn, colonize endemic, or native, hosts.